Matrix Tablets: An Effective Way for Oral Controlled Release Drug Delivery: Controlled drug delivery using matrix tablets - Saini Nisha,; George Mathew,; Joseph Lincy, (Iranian Journal of Pharmaceutical Sciences, 2012)
The purpose of this review article is to characterize all of the parameters regarding the types, polymers used, and release kinetics of matrix tablets. Matrix system was the earliest oral extended release platform for medicinal use. Matrix tablets are most commonly used methods to modulate the release profile of drugs. They are much desirable and preferred for such therapy because they offer better patient compliance, maintain uniform drug levels, reduce dose and side effects, and increase safety margin for high potency drugs. Hydrophilic polymer matrix systems are widely used for designing oral controlled drug delivery dosage forms because of their flexibility to provide a desirable drug release profile, cost effectiveness, and broad regulatory acceptance. However, the use of hydrophilic matrix alone for extending drug release for highly water soluble drugs is restricted due to rapid diffusion of the dissolved drug through the hydrophilic gel network. For such drugs it becomes essential to include hydrophobic polymers in the matrix system. This leads to the conclusion that matrix tablets seem to be most promising when developing an oral controlled release formulation.